Equilibrium studies for the removal of nitrates from aqueous solutions using acid treated sunflower seed husk (Helianthus annuus) - Chigondo, Fidelis; Sebata, E.; Maringe, A.; Moyo, Mambo; Nyamunda, Benias C. (Midlands State University, 2015)
Major adsorbent materials used for nitrate removal from polluted aqueous streams are expensive and difficult to regenerate. In this study, the possibility of using sunflower seed husk (helianthus annuus), as an alternative low cost biosorbent material to remediate nitrate pollution in waste water was investigated. The adsorbent was characterized before and after biosorption of nitrate ions by Fourier Transform-Infrared Spectroscopy (FT-IR). Functional groups such as hydroxyl, amino and carbonyl groups which are capable of binding nitrates were identified. Batch experiments were performed as a function of pH, sorbent dose, initial nitrate concentration, and contact time. The sorption capacity decreased with increasing sorbent dose while the percentage nitrate removal increased with increasing sorbent dose and also increased with increasing nitrate concentration. The optimum contact time was found to be 120 minutes, optimum biomass dose was 3.0 g and the optimum pH for nitrate removal was 2.0. The Freundlich and Langmuir adsorption isotherms were used to describe the equilibrium sorption data. The maximum adsorption capacity was 0.4924 mg/g according to the Langmuir model. The Langmuir model showed better representation of data, with correlation of determination value of 0.9941 compared to that of Freundlich of 0.8194. The findings of this investigation demonstrated the potential of using sunflower seeds husks in the removal of nitrates from aqueous solutions using a simple and cost effective treatment procedure.